A novel poxvirus isolated from an Egyptian fruit bat in Israel. Issue 3 (25th February 2020) - David, Dan; Davidson, Irit; Berkowitz, Asaf; Karniely, Sharon; Edery, Nir; Bumbarov, Velizar; Laskar, Orly; Elazari‐Volcani, Ron
Abstract: An Egyptian fruit bat ( Rousettus aegyptiacus ) from the Zoological Gardens, at Tel Aviv, Israel, showed pox‐like clinical signs including vesicular and nodular skin lesions on the wings. Cell culture isolation, histopathology, electron microscopy and molecular analysis, revealed the presence of a novel bat poxvirus. Future research is needed to determine whether this virus can affect human health. Abstract : An Egyptian fruit bat (Rousettus aegyptiacus) from the Zoological Gardens, at Tel Aviv, Israel, showed pox‐like clinical symptoms including vesicular and nodular skin lesions on the wings. Cell culture isolation, histopathology, electron microscopy and molecular analysis, revealed the presence of a novel bat poxvirus. Future research is needed to determine whether this virus can affect human health.